The role of high-sensitivity C-reactive protein serum levels in the prognosis for patients with stroke: a meta-analysis - Chen, Liuting; Wang, Min; Yang, Chanrui; Wang, Yefei; Hou, Bonan (Frontiers in Neurology, 2023)
Background The impact of high-sensitivity C-reactive protein (hs-CRP) as a biomarker of inflammation on the prognosis of stroke patients remains controversial, this study was conducted to evaluate the prognostic value of hs-CRP levels for patients with stroke. Methods PubMed, Web of Science, Embase, and Cochrane Library databases were searched from inception to October 28, 2022. Outcome measures were all-cause mortality, recurrent stroke, and poor prognosis. The relationship between the highest versus lowest levels of hs-CRP or per unit increment and outcomes as measured by risk ratio (RR) and corresponding 95% confidence intervals (CI). Results A total of 39 articles were eligible for meta-analysis. High hs-CRP levels at admission were associated with mortality among patients with acute ischemic stroke (AIS) [RR = 3.84, 95% CI (2.41 6.111); p < 0.001], risk of recurrent stroke [RR = 1.88, 95%CI (1.41 2.52); p < 0.001], and poor prognosis [RR = 1.77, 95% CI (1.59 1.97); p < 0.001]. The risk ratios for the association of per unit increase in hs-CRP levels with mortality, risk of recurrent stroke, and poor prognosis were as follows, respectively: 1.42 [95% CI (1.19–1.69); p < 0.001], 1.03 [95% CI (1.01–1.04); p = 0.003], and 1.27 [95% CI (1.10–1.47); p = 0.001]. For hemorrhagic stroke (HS), the risk ratios (RR) for the highest versus the lowest (reference) category of hsCRP or per unit increment to all-cause mortality were 4.36 [95% CI (1.38–13.73); p = 0.012] and 1.03 [95% CI (0.98–1.08); p = 0.238]. Conclusion Hs-CRP levels are strongly associated with mortality, risk of stroke recurrence and poor prognosis in stroke patients. Therefore, hs-CRP levels may contribute to the prognosis prediction of these patients.